Technology Retreats and the Politics of Social Media - Adam Fish (tripleC: Communication, Capitalism & Critique)
This essay examines weeklong technology retreats in Silicon Valley. These retreats embody digital healthism, which I define as the discourse that promotes the self-regulation of digital consumption for personal health. I argue that the self-regulation advanced by digital healthism insufficiently addresses the politics of media refusal. Technology retreats channel frustrations about social media use into opportunities for personal and corporate growth instead of political activism. I consider how technology retreats might participate in a dialogue about the regulation of social media platforms and companies by states. Evidence for these claims come from ethnographic research with the founders of a technology retreat in Silicon Valley.